Effect of integrated nutrient management on soil enzymes,microbial biomass carbon and bacterial populations under rice (Oryza sativa) –wheat (Triticum aestivum) sequence - NATH, D J; OZAH, B; BARUAH, R; BAROOAH, R C; BORAH, D K (The Indian Journal of Agricultural Sciences, 2026)
Key soil enzymes, microbial biomass carbon (MBC) and bacterial population were assessed to gain understanding the effects of integrated nutrient management (INM) under rice–wheat sequence grown during 2008 and 2009 in acid soils of Asom. Among the organic inputs, enriched compost (2 tonnes/ha) application demonstrated clear increase in Fluorescein di-acetate (FDA) hydrolase (8.91μg fluorescein/g/h), phosphomonoesterase (PMEase) (358.62 μg p-nitro phenol/g/h) and dehydrogenase (DH) (177.11 μg TPF/g/24 h) activities with only 25% of recommended N and P fertilizer under the sequence followed by compost (2 tonnes/ha) with biofertilizer inoculation. Likewise, highest MBC (183.66 μg/g) and maximum organic carbon (OC) (10.38 g/kg) accretion were obtained in the treatment received enriched compost (2 tonnes/ha) continuously for four crops. Compost (2 tonnes/ha) coupled with biofertilizers resulted maximum Azospirillum (5.79 log cfu/g), whereas enriched compost (2 tonnes/ha) favored elevated phosphate-solubilizing bacterial (PSB) (5.10 log cfu/g) population in the study. Significant correlations were existed among the enzymes as well as with buildup MBC, OC, Azospirillum and PSB population under the sequence. Application of compost (2 tonnes/ha) and biofertilizers with 25% recommended N and P fertilizer resulted significant increase in available N (234.11 kg/ha). Similarly, rock phosphate (RP) carrying enriched compost showed highest P (28.04 kg/ha) status of the soils. The overall multifaceted effects of different INM treatments that facilitated beneficial soil conditions in the present study reflected the significant increasing the grain yields of both rice (3.68 tonnes/ha) and wheat (0.98 tonnes /ha) even over the 100% NPK.